AL-‘ADZĀB DALAM ESKATOLOGI IBN ‘ARABĪ - Muhammad Yasir (Jurnal An-Nur, 2015)
The excitence of hell and doom that will be experienced in habitants of hell is one of doctrines that make up the integrity of islam teaching based on various verses of the Qur’an and hadits the prophet SAW, you can be sure that none of the muslims who deny the excitence of the doctrine of hell.however,wheter this fact also means that all muslims have the same perspective on this teaching.This discussion about the final fate of the in habitants of hell Ibn Arabi’s though would not have been successful without adequate attention about meaning and classification al-azab (hell) in the eschatological Ibn Arabi’s perspective.